2017
DOI: 10.1038/s41598-017-06194-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh adsorption and singlet-oxygen mediated degradation for efficient synergetic removal of bisphenol A by a stable zirconium-porphyrin metal-organic framework

Abstract: Bisphenol A (BPA), one of 23 most important endocrine disrupting chemicals, was efficiently removed and sequentially photodegraded by a zirconium-porphyrin metal–organic framework (MOF) catalyst under visible light for water treatment. Well control of photodegradation allows the kinetic separation of adsorption step and photodegradation step. Ultrahigh adsorption uptake of 487.69 ± 8.37 mg g−1 is observed, while efficient photodegradation could be observed within 20 min at the rate of 0.004 mg min−1. The syner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…Using scanning electron microscopy, we demonstrated that after 4 catalytic runs, the hexagonal rods were unaltered. The sizes of the crystals decreased slightly from 1.3 to 0.9 μm, and the edges became rounded, but the aspect ratio remained similar (3.5) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using scanning electron microscopy, we demonstrated that after 4 catalytic runs, the hexagonal rods were unaltered. The sizes of the crystals decreased slightly from 1.3 to 0.9 μm, and the edges became rounded, but the aspect ratio remained similar (3.5) …”
Section: Resultsmentioning
confidence: 99%
“…The sizes of the crystals decreased slightly from 1.3 to 0.9 μm, and the edges became rounded, but the aspect ratio remained similar (3.5). 53 PCN-222(Co) showed a high catalytic activity in the cycloaddition reactions, and a wide range of products were obtained under milder conditions compared to other…”
Section: Wementioning
confidence: 99%
“…In the catalytic degradation of industrial contaminants using MOFs, excellent results were obtained when using PCN-222(Zr) in the degradation of BPA. 330 High BPA adsorption uptake (488 mg g −1 ) was evidenced, while efficient photodegradation (99.9%) could be achieve within 20 min. The quite good reusability (five cycles) and wide range of suitable pH (from 2 to 10) make the Zr-porphyrin MOFs very practical for the photocatalytic water treatment processes, although the evaluation of their stability (metal and ligand leaching) under working conditions would be needed.…”
Section: Industrial Compounds/byproductsmentioning
confidence: 88%
“…In the catalytic degradation of industrial contaminants using MOFs, excellent results were obtained when using PCN-222­(Zr) in the degradation of BPA . High BPA adsorption uptake (488 mg g –1 ) was evidenced, while efficient photodegradation (99.9%) could be achieve within 20 min.…”
Section: Emerging Organic Pollutants Removal By Mofsmentioning
confidence: 99%
“…So far, commercial activated carbon is one of the most effective and commonly used adsorbents for organic pollutants removal from water systems . Slow pollutant uptake, energy-intensive regenerating, and efficient difference on types inescapably hamper the activated carbons refined use in micropollutant removal. , Several other novel adsorbents, such as Zr­(IV)-based metal–organic frameworks (MOFs), multiwalled carbon nanotubes, and surfactant-modified zeolite, have emerged for removing BPA. However, the materials mentioned were only tested in high-concentration BPA aqueous solution (usually >0.5 mM), or the operations need a long period of time (>1 h) for adsorption equilibrium. Therefore, it is desired to look for a superior strategy.…”
mentioning
confidence: 99%